Accountability of Regional Financial Management on the Suitability of Planning and Budgeting in Pamekasan Regency - Indah Dwi Kusrini; Habi Bullah (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
In public sector agencies, the achievement of regional financial management accountability is a demand for the implementation of good governance, regional financial management is one of the main lines in the implementation of regional government. So that many problems related to regional financial governance in government still often occur, one of which is that there are still discrepancies between local government planning and budgeting. This study aims to determine and analyze the accountability of regional financial management for the suitability of planning and budgeting in Pamekasan Regency based on Permendagri No. 19 of 2020. The data collection technique was to conduct interviews with structural officials of the R&D section of Bapperida Pamekasan Regency. As well as evaluating regional planning and budgeting documents according to the results of measuring the Regional Financial Management Index (IPKD). Based on the results of the study, it can be seen that there is an influence on dimension one related to the suitability of planning and budgeting documents on the financial management performance of the Pamekasan Regency Government so that the effect on financial management performance is less measurable, and can plan more carefully in the future. So that there is a mismatch in the RPJMD-RKPD Program indicator, the KUAPPAS - APBD program indicator, the RKPD - KUAPPAS ceiling indicator, and the KUA-PPAS and APBD Program ceiling indicators. In the analysis of the RKPD-KUAPPAS program suitability indicators.